Evaluation of selected developmental samples of chelating agents on model washing - Bayerová, Petra; Burgert, Ladislav; Černý, Michal; Hrdina, Radim; Hrubešová, V. (My University, 2018)
This work presents the results of model washing with addition of selected developmental samples of chelating agents. The washing was realized in hard water of 22 °dH (given in German degrees of hardness). After 20× repeated washing the content of ash and Ca2+ ion were determined. The image of fabric after the model washing was evaluated by means of images from a scanning electron microscope.
Vliv vybraných vývojových vzorků chelatačních prostředků na modelové praní
Keywords: chelating agents; washing of textile materials; model washing; chelatační prostředky; praní textilních materiálů; modelové praní